2017
DOI: 10.1016/j.mvr.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of coffee on skin blood flow and microvascular function

Abstract: Caffeine, as ingested by drinking caffeinated coffee acutely improves endothelium-dependent microvascular responses in the forearm skin, while endothelium-independent responses to PORH and SNP iontophoresis are not affected. Blood flow in the fingertip decreases markedly during the first hour after drinking caffeinated coffee compared to decaffeinated coffee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
(58 reference statements)
1
17
1
Order By: Relevance
“…Like coffee, tea also requires hot water for brewing. 35 Increased sympathetic excitability and vasodilatation were thought to be involved in the occurrence and development of flushing and subcutaneous telangiectasia in rosacea. Lukewarm or cool is more common in our country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like coffee, tea also requires hot water for brewing. 35 Increased sympathetic excitability and vasodilatation were thought to be involved in the occurrence and development of flushing and subcutaneous telangiectasia in rosacea. Lukewarm or cool is more common in our country.…”
Section: Discussionmentioning
confidence: 99%
“…33 Studies reported that caffeine played a significant role in sleep deprivation and activation of sympathetic nerves, 34 mediating skin vasodilatation through stimulating iontophoresis of acetylcholine. 35 Increased sympathetic excitability and vasodilatation were thought to be involved in the occurrence and development of flushing and subcutaneous telangiectasia in rosacea. 36 Clinically, a-adrenergic or b-adrenergic receptors blockers contribute to telangiectasia by modulating neuronal dysregulation in rosacea.…”
Section: Discussionmentioning
confidence: 99%
“…After drinking a single cup of coffee, endothelium-dependent vasodilatation in the skin is acutely enhanced and blood flow in the fingertip is substantially reduced [24]. Intake of caffeine through drinking caffeinated coffee acutely augments microvascular reactivity [25]. It was therefore decided to include caffeine at a dose of 150 mg (2 cups of strong coffee) into this study protocol.…”
Section: Caffeinementioning
confidence: 99%
“…Caffeine elevated blood pressure and decreased finger blood flow and at the same time enhanced the PORH of finger blood flow. In contrast, the study by Tesselaar and co-workers reported no change in blood pressure, heart rate, or PORH [22].…”
Section: Introductionmentioning
confidence: 99%